2023
DOI: 10.1108/ejim-01-2023-0064
|View full text |Cite
|
Sign up to set email alerts
|

Executive compensation incentives, innovation openness and green innovation: evidence from China's heavily polluting enterprises

Abstract: PurposeA green innovation strategy is an important step for enterprises to balance economic and environmental. As the executors of strategic decisions, the attitude and capabilities of senior managers determine the effectiveness of implementing green innovation. Therefore, this paper aims to explore the relationship between executive compensation incentives and green innovation.Design/methodology/approachBased on the data of heavily polluting enterprises listed in China's A-share market from 2015 to 2020, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…This can reduce the problem of agency. Zhao et al (2023) found that providing compensation incentives to management can increase their willingness to innovate [49]. Atallah et al (2021) found a positive correlation between innovation and incentive measures [50].…”
Section: Research Hypothesis 331 Shareholders and Executives Need To ...mentioning
confidence: 99%
“…This can reduce the problem of agency. Zhao et al (2023) found that providing compensation incentives to management can increase their willingness to innovate [49]. Atallah et al (2021) found a positive correlation between innovation and incentive measures [50].…”
Section: Research Hypothesis 331 Shareholders and Executives Need To ...mentioning
confidence: 99%
“…According to the enterprise lifecycle theory (Miller and Friesen, 1984) [15], firms evolve through dynamic growth stages, each impacting TMTEA's role in corporate GI differently. During the growth phase, companies bolster competitiveness through substantial investments, such as R&D, product promotion, and production capacity expansion (Zhao et al, 2023) [31]. Initially, TMTEA's approach to environmental concerns might be limited.…”
Section: Growth Periodmentioning
confidence: 99%
“…In the mature stage of a firm's lifecycle, it reaches its maximum scale, employee value, and internal governance efficiency (Zhao et al, 2023) [31]. Fortified by a robust resource base and capabilities, mature enterprises adeptly meet green consumer demands, fostering sustainable development.…”
Section: Mature Periodmentioning
confidence: 99%
See 2 more Smart Citations